Pengaruh Metode Pembelajaran Inkuiri Terbimbing Berbasis Phet Simulation Terhadap Hasil Belajar Kimia Materi Asam Basa Pada Siswa Kelas XI F SMA Negeri 1 Alas - Vidia, Nila Vidia Ekayanti; Haris, Mukhtar; Sofia, Baiq Fara Dwirani (Chemistry Education Practice, 2025)
This study aims to analyze the effect of guided inquiry learning method based on PhET simulation on the learning outcomes of chemistry on acid-base material in class XI F students of SMA Negeri 1 Alas. The type of experimental research is pre-experimental with one group pretest-posttest research design. The population is 165 students with a sampling technique using purposive sampling, namely class XI F4 which consists of 33 students. Class determination is based on the number of students who do not meet the Learning Objective Completion Criteria (KKTP). Data collection techniques use test instruments, active observation, and questionnaires. The average pretest score is 21.5152 and the average posttest score is 79.3333. The results show that the average N-gain score is 0.71 with a high category. The t-test results obtained a Sig. (2-tailed) value of 0.000 <0.05, so H0 is rejected and Ha is accepted. Meanwhile, the percentage of student activity was 74.02% with a good category and student responses to learning were included in the very interested category with an average interest of 84.02%. The results of this study can be concluded that the use of guided inquiry learning methods based on PhET simulation on acid-base material can improve the chemistry learning outcomes of class XI F students of SMAN 1 Alas.